The Dermatological Effects of Vitamin D: Addressing Pore Size and Skin Roughness - Sukmawati Tansil Tan; Alexander Halim Santoso; Ayleen Nathalie Jap; Alicia Herdiman; Friliesa Averina; Farell Christian Gunaidi (Universitas Muhammadiyah Manado, 2025)
Vitamin D, or calciferol, is a fat-soluble vitamin produced endogenously when ultraviolet (UV) light triggers its synthesis in the skin. It also comes from food and supplements, existing as D2 (ergocalciferol) and D3 (cholecalciferol). Both forms convert into the active form, calcitriol, in the liver and kidneys, with D3 more effectively raising blood levels. Vitamin D supports bone health, regulates cellular functions, and offers anti-inflammatory, antioxidant, and neuroprotective benefits. It improves skin health by regulating oil production, soothing inflammation, promoting skin renewal, and strengthening the skin barrier. Deficiency (<20 ng/dL) weakens the skin barrier, causing dryness and roughness. The global prevalence of vitamin D deficiency is rising, with Southeast Asia, including Indonesia, experiencing rates between 35.1% and 91.7%. This study explores the relationship between vitamin D levels and skin health, focusing on pores and roughness in geriatric populations. This cross-sectional study analyzed 26 elderly, measuring vitamin D levels (Vitamin D 25-hydroxy (25(OH)D), skin pore size, and roughness (RGB analysis), with Spearman and partial correlation assessing relationships while controlling for age. Bivariate analysis showed a significant positive relationship between vitamin D levels and pore size (p = 0.03) and a strong, statistically significant relationship between pore size and skin roughness (p < 0.01). Vitamin D influences skin health, including pore size and texture. Monitoring vitamin D levels enables early intervention, improving skin appearance, reducing roughness, and preventing complications from vitamin D deficiency.